Vertical Distribution of Heavy Metals in Coastal Sediment: A Record of the Changing Input in the Estuarine of the Semarang Flood Canal - Fitri Budiyanto (Marine Geological Institute of Indonesia, 2018)
Sediment plays an important role in archiving contaminant like heavy metals and couldrecord metal contamination in sediment due to land-based input such as flood canals of Semarang. Thisstudy was to understand the changing record of heavy metals’ contamination in coastal sediment and toassess the sediment quality. Two core sediments, from two different sites, were collected up to 80 cm in depthand, subsequently, sectioned within a 5 cm interval. A digestion system followed by AAS measurement, wasused to determine the metal concentrations, Enrichment Factor (EF) was applied to assess sediment quality.The sediment fraction and metals concentration revealed the changing of input and deposition process alongsediment cores in East Flood Canal (EFC) and West Flood Canal (WFC). There was an alteration ofsediment composition in which the proportion of sediment composition moved to finer size in EFC and apulse of coarser-finer-coarser size of sediment composition was observed in WFC. In general, higherconcentrations of Fe, Cd, Cu, Ni and Zn were observed differently with Pb concentration. Ni along bothsediment cores was unenriched (EF<1), whereas Cd, Cu, Pb, and Zn were classified minor to moderateenrichment. Thus, the source and deposition processes of these Fe, Cd, Cu, Ni and Zn were differentcompared with those of Pb.Keyword: flood canal, Semarang, heavy metal, Enrichment FactorSedimen memiliki peran sebagai tempat penyimpanan bahan pencemar seperti logam berat dan studiatas pencemaran logam berat dalam sedimen di banjir kanal kota Semarang belum banyak dilakukan. Sehinggatujuan dari penelitian ini adalah untuk mengetahui sejarah pencemaran dengan melihat distribusi vertikal kemudianmenilai status logam berat dalam sedimen di muara banjir kanal barat dan banjir kanal timur kota Semarang. Untukmenjawab tujuan penelitian, telah dilakukan pengambilan 2 sampel sedimen inti hingga kedalaman 80 cm kemudiansedimen tersebut diambil tiap interval 5 cm. Metode peleburan yang diikuti pengukuran dengan AAS dilakukanuntuk mengukur konsentrasi logam dan Enrichment Factor (EF) dihitung untuk menilai kualitas sedimen. Fraksisedimen dan konsentrasi logam berat menunjukkan perubahan masukan dan proses deposisi di sepanjang sedimen intiyang dianalsis dari Banjir Kanal Timur (BKT) dan Banjir Kanal Barat (BKB). Tampak adanya perubahankomposisi sedimen dimana sedimen di EFC cenderung menjadi lebih halus sementara tampak adanya fluktuasikomposisi sedimen di WFC dari kasar-halus-kasar. Masing-masing logam menunjukkan pola yang berbedawalaupun konsentrasi Fe, Cd, Cu , Ni dan Zn tinggi tampak di periode energi yang lebih tinggi dan konsentrasi Pbtinggi teramati sema periode energi rendah. Ni di kedua sedimen inti masih berada pada konsentrasi alami(EF<1),tetapi Cd, Cu, Pb dan Zn telah mengalami pengayaan minor hingga moderat. Informasi tersebut dapatmenunjukkan sumber dan proses deposisi Fe, Cd, Cu, Ni dan Zn berbeda dengan Pb.Kata kunci: Banjir kanal, Semarang, logam berat, Enrichment Factor.